violencia en Gascuña y los enfrentamientos anglo-navarros (siglos XIII y XIV) - Aparicio Rosillo, Susana (Huarte de San Juan. Geografía e Historia, 2007)
This article tries to establish an outlook of violence in medieval conflicts, mainly in Gascony area, through the example of a document preserved in the General Archives of Navarre. It contains the detailed claims written by the kings of Navarre, Thibalt I, and England, Henri III, in answer to the damages caused as a result of the war developed between years 1237 to 1248 in the English part of Gascony. Many performances of violence are briefed in this text: kidnappings, murders, injuries to gentlemen, servants... produced as much in rural lands as in cities like Bayonne.